Asthma knowledge, attitudes, and quality of life in adolescents. Issue 4 (October 1995) - Gibson, P G; Henry, R L; Vimpani, G V; Halliday, J
Abstract : Adolescents with asthma, their peers, and their teachers were studied in order to establish the level of knowledge concerning asthma and its management, their attitudes towards asthma, and the degree quality of life impairment due to asthma. A community survey was conducted among year 8 high school students (n = 4161) and their teachers (n = 1104). There was a good response rate to the questionnaires from students (93%) and teachers (61%). Twenty three per cent of students had asthma and this caused mild to moderate quality of life impairment, particularly with strenuous exercise. Asthma was provoked by passive smoke exposure in 30% of asthmatic students and up to 51% of students avoided situations because of asthma triggers. Asthma knowledge was low in teachers (mean score 14.90 out of a possible 31), students without asthma (11.25) and students with asthma (14.50). Specific knowledge on the prevention and treatment of exercise induced asthma was poor. There was a moderate degree of tolerance towards asthma among all three groups. Most considered internal locus of control as important, although students without asthma also considered chance to be a determinant of outcomes for people with asthma. Asthma is a common cause of quality of life impairment among year 8 high school students. Although specific knowledge on asthma is low, students and teachers hold favourable attitudes towards asthma. There are opportunities to intervene and improve asthma management among adolescents.